A STUDY OF POPULATION PRESSURE TOWARD AGRICULTURE LAND IN MOJOLABAN SUBDISTRICT, SUKOHARJO – CENTRAL JAVA - Agus Sudargono; Pranichayudha Rohsulina; Talitha Rahmawati; Agung Hidayat (USN Kolaka, 2020)
Indonesia is an agricultural country in the tropic area with a high potential of agricultural land. This condition is a good ecosystem for human, animal and plant life. With all those potentials, the population in Indonesia has reached more than 260 million people currently. Surely, such a large population brings logical consequences in which a large amount of land must be provided by the State to support the housing needs and to meet the food and clothing needs. As a matter of fact, the population of Indonesia continues to increase over the time. The increase in population in many areas has caused the conversion of agricultural land into residential land. Therefore, the agricultural land continues to have pressure constantly. The Population pressure to agricultural land is a comparison between the number of people and the minimum land area to be able to live properly. This study aims to analyse the variations of population pressure on agricultural land in each village in Mojolaban Sub-District. The research method used to analyse the population pressure was by utilizing the formula of Otto Sumarwoto I, where residents are considered to only live on cultivated agricultural land. The results showed that population pressure toward agricultural land in Mojolaban Sub District was high. There were 11 villages and 4 villages that were categorized as high and low population pressure on agricultural land respectively.